Analisis Manajemen Risiko Pada PT Bank Negara Indonesia Tbk - Rahmadani Rahmadani (Jurnal Akuntansi, Manajemen, Bisnis dan Teknologi, 2025)
The aim of this research is to find out and analyze how risk management is carried out at PT Bank Negara Indonesia which is listed in the banking sector on the Indonesia Stock Exchange (BEI) in 2022. Methodology This research is qualitative and descriptive. The results of the analysis show that the management of a company can be influenced by risk management. Where risk management is directly proportional to company performance. Risk management has been successfully implemented by the banking industry, especially PT Bank Negara Indonesia, Tbk. The banking sector, namely BNI, has implemented standardized risk management. Proven based on report data in 2022, PT. Bank Negara Indonesia, Tbk has implemented both national and international risk management standards. BNI's implementation of risk management is known as 4 pillars.